1991
DOI: 10.1093/ndt/6.4.232
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Markers in Diarrhoea-Associated Haemolytic-Uraemic Syndrome: Initial Neutrophil Count, Human Neutrophil Elastase and Von Willebrand Factor Antigen

Abstract: The observed increase in plasma von Willebrand factor antigen (vWF:Ag) in patients with the haemolytic-uraemic syndrome is presumed to be secondary to endothelial damage, which is a central event in these diseases. As the prognostic value of such changes has not been previously evaluated, vWF:Ag has been measured in plasma from children reported to a national survey of haemolytic-uraemic syndrome. Human neutrophil elastase was also measured, as an initial neutrophilia has been shown to have prognostic value in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Besides the cytotoxic effects of Stx, the inflammatory response mediated by neutrophils (PMN) also contributes to HUS evolution [3]. HUS patients show a high peripheral PMN count, which correlates with a poor prognosis [4]. Moreover, these cells have shown signs of previous activation, indicated by a reduced expression of different membrane molecules and intracellular components, as well as impaired cytokine-induced responses [5].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the cytotoxic effects of Stx, the inflammatory response mediated by neutrophils (PMN) also contributes to HUS evolution [3]. HUS patients show a high peripheral PMN count, which correlates with a poor prognosis [4]. Moreover, these cells have shown signs of previous activation, indicated by a reduced expression of different membrane molecules and intracellular components, as well as impaired cytokine-induced responses [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, histological studies of gastrointestinal tissue of patients infected with STEC show neutrophil infiltration in the lamina propria and crypts (18,23,24,42). High IL-8 levels have been noted in HUS patients, and it was suggested that IL-8 expression was, at least in part, responsible for neutrophil recruitment in the disease (13,14,15,32,50). Rabbit models of STEC infection have implicated intestinal neutrophils as contributing to pathogenesis (12,46).…”
mentioning
confidence: 99%
“…Severe thrombocytopenia is uncommon but prolonged thrombocytopenia for more than 10 days is associated with long-term renal picture. Factor VIII levels do not correlate with clinical outcome [12]. Table 5 summarizes laboratory tests/ investigations according to Haematology specialty.…”
Section: Hus and Laboratory Tests/ Investigationsmentioning
confidence: 99%